(untitled) (International Journal of Education in Mathematics, Science and Technology, 2026)
There is need for increased focus on geometric transformations and symmetry in primary and secondary education, as well as increased research to support learning and teaching of geometric transformations. To identify directions for future research and teaching, we set out to map the research that has already been conducted and to identify key areas of focus and opportunity going forward. Toward these goals, this systematic review examines 62 peer-reviewed articles on teaching and learning about 2D geometric transformations and symmetry since 1990. To guide our review, we use the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) protocol. The review explores the research in terms of: (a) how students learn about transformations, (b) how teaching about transformations has been conceptualized, (c) how media have been leveraged to support learning about transformations, and (d) which theoretical frames have been leveraged and how have those frames shifted over time. Discussion and conclusions consider key areas of growth for the field going forward to better support teachers and students learning about symmetry and transformations.